Localized histopathological effects of high-salt intake on the aorta and kidney in rats - Oh, ChangHwa; Hong, Sung Jun; Kim, Jeonghun; Kim, Yu-Gyeong; Lee, Hye-Won; Kim, Dokyoon; Park, Eunkyoung; Kim, Taekyung; Shon, Young-Min (Frontiers in Physiology, 2025)
BackgroundExcessive dietary sodium intake is a major global public health concern, responsible for approximately 1.89 million deaths annually. High salt consumption disrupts systemic homeostasis and elevates blood pressure, thereby increasing the risk of cardiovascular diseases, including arterial stiffness, atherosclerosis, heart failure, myocardial infarction, and stroke. Additionally, excessive salt adversely affects renal structure and function by inducing glomerular and tubular injury, promoting extracellular matrix (ECM) accumulation and fibrosis, ultimately accelerating chronic kidney disease.ObjectiveTo investigate the histopathological changes and differences in the heart, aorta and kidneys of Sprague Dawley rats subjected to normal and high-salt diets.MethodsThis experiment examined male Sprague Dawley rats, aged 6 weeks, which were divided into a normal diet group (control, n = 9) and a high-salt diet group (high salt, n = 10), and were observed over 12 weeks. Blood pressure (BP) changes were measured, and histological analyses of the heart, aorta and kidney tissues were performed.ResultsOur results revealed localized histological alterations in the aorta and kidneys following high-salt intake. Aortic wall thickening was observed specifically at Zone 0 (A2, p < 0.05), without significant collagen deposition. In the kidneys, the high-salt group showed significant capsular space narrowing (p < 0.05), glomerular hypertrophy, and tubular dilatation, accompanied by increased interstitial collagen deposition (p < 0.0001), indicative of renal fibrosis. In contrast, no significant pathological or fibrotic changes were detected in the left ventricle aside from body weight–related variation.ConclusionThese findings indicate that a high-salt diet induces localized histopathological changes in specific regions of the aorta and kidneys. This study provides foundational data for understanding the pathological mechanisms of high-salt intake and offers insight into potential prevention strategies for salt-induced aorta and renal injury.